National planning for GHG mitigation in agriculture: a guidance document - Wilkes, Andreas; Tennigkeit, Timm; Solymosi K (Food and Agriculture Organization of the United Nations, 2013)
A significant proportion of developing countries have expressed an interest in greenhouse gas (GHG) mitigation in the agriculture sector. However, compared to mitigation planning in some other sectors, progress with developing agricultural mitigation plans and the allocation of climate finance to the agriculture sector have been limited. The purpose of this guide is to provide national policy makers, advisors and other stakeholders in the agriculture sector with an introduction to the main mitigation planning approaches and the key elements that may need to be considered in the planning process. This guide describes two of the main approaches to GHG mitigation planning in developing countries: Low-Emission Development Strategies (LEDS) and Nationally Appropriate Mitigation Actions (NAMAs). It explains the possible relationships between them and their status within the United Nations Framework Convention on Climate Change (UNFCCC). National mitigation planning processes have policy, technical and institutional dimensions that need to be addressed in an integrated and iterative manner. For each of these dimensions four key elements are outlined. Examples from mitigation planning processes in developing countries are provided to illustrate the range of options for addressing these key elements in country-specific ways. Special considerations for including smallholder farmers in the planning process are highlighted. This guide may be read as a companion document to the recent publication, National integrated mitigation planning in agriculture: A review paper, which reviewed LEDS in 18 developing countries and agricultural NAMAs in 30 countries. The Review Paper, prepared with support of CCAFS and FAO, can be accessed here: http://www.fao.org/docrep/017/i3237e/i3237e.pdf.